2011
DOI: 10.1007/s10903-011-9493-2
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Prevention: Culture, Context, and Cervical Cancer Screening among Vietnamese American Women

Abstract: Few studies have investigated what Vietnamese American women believe about the Pap smear or how those beliefs might influence behavior. Thirty-one Vietnamese American women recruited through snowball sampling were interviewed about their beliefs regarding the Pap smear. Interviews were qualitatively analyzed using a theoretically informed, inductive approach. The women interviewed emphasized the importance of primary prevention of disease through culturally-informed personal health regimens. They were also lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…The current study's findings confirm the results from a previous study with VA women about their heavy reliance on personal health regimens including vaginal washing as a means of disease prevention (Gregg et al, 2011). The current study's findings add to the literature through highlighting that "washing" is a cultural tradition that is passed down; for example, from mother to daughter, or shared with friend to friend.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The current study's findings confirm the results from a previous study with VA women about their heavy reliance on personal health regimens including vaginal washing as a means of disease prevention (Gregg et al, 2011). The current study's findings add to the literature through highlighting that "washing" is a cultural tradition that is passed down; for example, from mother to daughter, or shared with friend to friend.…”
Section: Discussionsupporting
confidence: 86%
“…Also, VA women who reported an income less than 200% below the federal poverty level were less likely to obtain regular CC screening than other Asian American women (Chawla et al, 2015). Our previous qualitative study reported that VA women relied on personal health regimens such as vaginal washing as a means of CC prevention (Gregg, Nguyen-Truong, Wang, & Kobus, 2011). Hence, VA women may need culturally and linguistically appropriate counseling.…”
Section: )mentioning
confidence: 94%
“…) and that a large proportion of Vietnamese Americans are unfamiliar with cervical screening (Gregg et al . ). Jenkins et al .…”
Section: Discussionmentioning
confidence: 97%
“…Further studies are needed to better understand how these culturally associated beliefs influence cervical cancer screening rates and whether this influence depends on other contextual variables. Gregg, Nguyen‐Truong, Wang, and Kobus () found that though VAW's culturally associated beliefs (e.g., personal preventive health regimens) did not directly cause VAW to seek or avoid Pap tests, the beliefs did influence screening behaviors to a greater or lesser degree that depended on contextual variables such as personal finances, logistics, and emotional states. Programs targeting VIW should specifically address identified barriers as this may increase the likelihood of success in Pap testing participation.…”
Section: Discussionmentioning
confidence: 99%
“…Gregg et al. () found that though VAW respected and valued doctors’ ability to detect and treat disease, medical care became less urgent for VAW who strongly believed in the protective efforts of their personal preventive health regimens and who had other options when access to medical care was difficult. Primary HCPs should be reminded of their essential role in increasing adherence to cervical cancer screening.…”
Section: Discussionmentioning
confidence: 99%